Influence of Border-Keepers’ Support on Work-Family Enrichment of Preschool Teachers in China: The Mediating Role of Work-Family Boundary Flexibility - Peng, Qian; Lian, Chongyan; Zhang, Limin (Frontiers in Psychology, 2022)
Based on work-family border theory and work-home resource theory (W-HR), this paper examines the impact of border keeper’s support (organizational support and family support) on work-family enrichment and whether or how work-family boundary flexibility mediates the relationship between border keeper’s support and work-family enrichment. A sample of 504 preschool teachers in Guangdong province, China completed questionnaires. The research results show a two-way process of work-family enrichment for preschool teachers in China. Organizational support was directly and significantly correlated with work-to-family enrichment (WFE), and family support was significantly and directly correlated with family-to-work enrichment (FWE). Organizational support had no significant positive predictive effect on work boundary flexibility which has a significant positive predictive effect on WFE. Family support had a significant positive predictive effect on family boundary flexibility which had a significant positive predictive effect on the FWE. In addition, the study found that family boundary flexibility mediates the relationships between family support and FWE whereas work boundary flexibility did not mediate the relationships between organizational support and WFE. The above research results are partly consistent with the existing research, and partly inconsistent, which is related to the profound influence of traditional culture in Chinese society and the current situation of preschool teachers in China. Such findings have important implications for improving the work-family enrichment of preschool teachers.